2016
DOI: 10.1038/srep22974
|View full text |Cite
|
Sign up to set email alerts
|

Structural health monitoring (vibration) as a tool for identifying structural alterations of the lumbar spine: a twin control study

Abstract: Structural health monitoring (SHM) is an engineering technique used to identify mechanical abnormalities not readily apparent through other means. Recently, SHM has been adapted for use in biological systems, but its invasive nature limits its clinical application. As such, the purpose of this project was to determine if a non-invasive form of SHM could identify structural alterations in the spines of living human subjects. Lumbar spines of 10 twin pairs were visualized by magnetic resonance imaging then asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In another study, Van Engelen et al (2012) performed a quasi-static test to assess the quasi-static stiffness of six cadaver human spines and a modal test to determine the Eigen frequencies of the samples for flexion-extension, lateroflexion, and axial rotation. Kawchuk et al (2016) executed an experimental modal test on living human subjects to recognize structural alterations in their spines. Mondal and Arunachalam (2020) proposed a 3D FE model of a seated human driver inside a vehicle simulating the human segments with ellipsoidal portions in Abaqus.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Van Engelen et al (2012) performed a quasi-static test to assess the quasi-static stiffness of six cadaver human spines and a modal test to determine the Eigen frequencies of the samples for flexion-extension, lateroflexion, and axial rotation. Kawchuk et al (2016) executed an experimental modal test on living human subjects to recognize structural alterations in their spines. Mondal and Arunachalam (2020) proposed a 3D FE model of a seated human driver inside a vehicle simulating the human segments with ellipsoidal portions in Abaqus.…”
Section: Introductionmentioning
confidence: 99%
“…Given the above, there is a significant inability to quantify shock absorption properties using diagnostic methods commonly applied in health care. 11 …”
Section: Introductionmentioning
confidence: 99%
“…To fill this void, several authors have identified established engineering techniques used in evaluating mechanical assemblies and adapted them for use in the analysis of human locomotor system function. 11 14 It seems that the spine shock absorption properties can be directly expressed in the frequency domain as the transmissibility of vibration through the spinal column. 15 These vibrations can be measured with accelerometers attached to the skin over the spine bony prominence, which has been previously validated against pins inserted directly into the bone, with promising results.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this invasive approach has limited clinical application. In addition to model experiments, a previous clinical study using surface-based accelerometers was able to demonstrate that signals from different pathologies are unique in human twins 12 . In this study, five sets of discordant twins showed unique vibration signals in contrast to five sets of concordant twins, where signals overlapped.…”
mentioning
confidence: 99%